Experimental study on mechanical properties for a three-phase polymer composite reinforced by glass fibers and titanium oxide particles - Duc, Nguyen Dinh; Minh, Dinh Khac (Vietnam Journal of Mechanics, 2011)
Nowadays, composite materials are applied in many fields. The physico-mechanical properties of the material can be improved by adding reinforced fibers and particles. Many scientists pay attention to the calculation for elastic modules of three-phase composite materials. This report presents the experimental results for some elastic modules of three-phase polymer composite reinforced with glass fibers and titanium oxide particles of different volume ratios. A comparison between experimental and theoretical results shows good agreement